Proximate Analysis of Merang Mushrooms (Volvariella volvacea) Cultivated on Corncob and Rice Bran Media - Sintia Puspa Dewi; Nunung Eni Elawati; Catur Retno Lestari (HM Publisher, 2022)
Merang Mushroom (Volvariella volvaceae) is one of the edible mushrooms. The nutritional content of merang mushrooms makes this mushroom has potential as a medicine and food supplement. Merang mushrooms are known to function as antioxidants, antidiabetic, antiviral, and can lower cholesterol. The purpose of the research is to find out the nutritional content of merang mushrooms that are cultivated in corncob media with the addition of rice bran. The analysis used was proximate analysis to determine moisture, ash, and fiber content using the AOAC method, fat content analysis using the Soxhlet method, protein content analysis using the Kjeldahl method, and carbohydrate analysis (By difference). The results of the analysis were 2.17% ash content, 85.14% water content, 3.65% crude fiber content, 1.99% fat content, 2.7% crude protein content, and 8.0% carbohydrate content. Based on research, it can be said that mushroom has a good nutritional content that can provide health benefits.